Analisis Realisasi Anggaran Pendapatan dan Belanja Daerah Pemerintah Kota Medan - Lubis, Putri Kemala Dewi; Sinaga, Enwanda Nia Monika Br; Effendi, Dicky; Daniel, Hwan; Sintia, Iin (Ikatan Da'i Indonesia, 2024)
This research aims to determine the Realization of the Regional Revenue and Expenditure Budget of the Medan City Government FY 2017-2021. This research uses a qualitative approach using Medan City Regional Income and Expenditure data 2017-2021. From the results of the discussion, it was found that the realization of Medan City's regional income still had not reached the set target, with the realization percentage below 100% during that period. The COVID-19 pandemic had a significant impact on regional income, especially in 2020, which caused a decrease in Original Regional Income and transfer income. Realization of Medan City regional spending tends to be below the budgeted budget, although there was an increase in 2019 and a decrease in 2020 due to the handling of the pandemic. Direct and indirect spending reflects the policies and strategies of the Medan City government in facing various challenges, especially related to handling the pandemic.